INFLUENCE OF MICROADDITIVES ON MECHANICAL PROPERTIES OF POLYMER COMPOSITES FOR WATER TRANSPORT VEHICLES - Buketov, Andrii; Strelchenko, Vladyslav (Problems of Friction and Wear, 2025)
The study investigates the influence of microdispersed titanium-aluminum charge synthesized by high-voltage electrospark method on the adhesive and mechanical properties of epoxy composites. Optimal filler concentrations were determined that ensure significant improvement in the operational characteristics of the materials. It was established that the introduction of 0.04 wt.% microdispersed charge provides maximum improvement in composite properties: adhesive strength under tension increases by 53%, adhesive strength under shear improves by 27%, and residual stress level rises by 33%. These indicators demonstrate the formation of strong interfacial bonds between the filler and matrix, significantly enhancing the composite's adhesion to metal substrates. Additionally, improvements in mechanical properties of the epoxy composite were observed when introducing the filler at 0.2…0.5 wt.%. The study revealed a 40…56% increase in ultimate strength, 33…40% improvement in impact toughness, and stable elastic modulus (without significant changes). This indicates that this concentration range allows achieving an optimal balance of strength, impact resistance, and elastic characteristics of the obtained materials. The obtained results confirm the effectiveness of using microdispersed charge for modifying epoxy composites. Precise dosage of the filler enables control over material properties, ensuring high operational performance. These findings hold significant importance for industrial applications of modified epoxy composites. Particular attention should be paid to the following aspects. The process of introducing microdispersed charge doesn't require complex equipment, and the forming method allows precise control of filler concentration. From an economic perspective, using optimal concentrations (0.04…0.5 wt.%) minimizes filler costs, suggesting reduced operational and maintenance expenses for transport equipment. The research proved the high effectiveness of microdispersed titanium-aluminum charge for modifying epoxy composites. The established optimal filler concentrations allow substantial improvement of mechanical and adhesive properties without significant changes to the technological process. The results open new possibilities for creating high-performance composite materials with tailored characteristics.